Analysis of DNA damage response in mouse embryonic stem cells - Xu, Ruiping (2015)
Embryonic stem cells have the intrinsic capacity to proliferate indefinitely and this renders them highly susceptible to DNA damage in the form of double strand breaks (DSBs). DSBs are recognized as the most lethal DNA damage lesion and this put ESCs in a vulnerable position. It was reported that the age dependent accumulation of DNA damage in stem cells contributes to loss of stem cells function as they aged. The downstream signals and effects in respond to DNA damage are important determinants of stem cell functionality, but this have yet to be completely understood. In this study, the DNA damage response of mESCs as it aged in vitro is investigated to analyze any age-dependent effects on DNA damage response. These responses in ESCs include DNA repair, differentiation, cell-cycle arrest and apoptosis. In this study, γ-H2AX assay was employed to study the response and repair of DSBs. The pluripotency marker SSEA1, and differentiation marker SSEA4 of mESCs were used to analyze the changes in pluripotency and differentiation. The passages used in this study are the earlier passages (p5, p10 and p15) of D3 mESCs. Our results reported no significance difference in DNA damage response as mESCs aged in vitro. This implied that the early passages of mESCs responded similarly to DNA damage.